Autonomy and School Management in the Spanish Context - Joaquín Gairín Sallán (LED Edizioni Universitarie, 2015)
Processes of educational decentralisation often arise in the development of institutional autonomy. Through this, a contextualisation of education is sought as well as a greater involvement of its key players. School autonomy has been developing since 1985, when school boards were established and they had to select principals and school managers. Although legislative changes have continued to occur, there has been little progress in curricular autonomy, and the development of organisational and economic-administrative autonomy continues to be a challenge in the Spanish context. The autonomous community management model that has been set up is linked to the choice of principals for a short time. Although the Autonomous Community of Catalonia has developed a more professional proposal, including prior training and presentation of management projects, it certainly continues to be a malfunction in the education system and a cause for constant controversy. This text reviews the creation and development of the proposals that have been made on autonomy and management in the Spanish context.